Possible Therapeutic Utility of anti-Cell Adhesion Molecule 1 Antibodies for Malignant Pleural Mesothelioma - Hagiyama, Man; Mimae, Takahiro; Wada, Akihiro; Takeuchi, Fuka; Yoneshige, Azusa; Inoue, Takao; Kotoku, Naoyuki; Hamada, Hironobu; Sekido, Yoshitaka; Okada, Morihito; Ito, Akihiko (Frontiers in Cell and Developmental Biology, 2022)
Malignant pleural mesothelioma (MPM) is a highly aggressive malignant tumor, and the effective therapeutic drugs are limited. Thus, the establishment of novel therapeutic method is desired. Considerable proportion of MPMs are shown to express cell adhesion molecule 1 (CADM1), and to use CADM1 to bind to and proliferate on the pleural mesothelial surface, suggesting that CADM1 is a possible therapeutic target. Here, anti-CADM1 ectodomain chicken monoclonal antibodies, 3E1 and 9D2, were examined for their possible therapeutic utility. The full-length form of CADM1 was expressed in eight out of twelve human MPM cell lines. MPM cell lines were cultured on a confluent monolayer of mesothelial MeT-5A cells in the presence of 9D2, the neutralizing antibody. 9D2 suppressed the cell growth of CADM1-positive MPM cells with the loss and aggregation of CADM1 molecules on the MPM cell membrane, but not of CADM1-negative MPM cells. Co-addition of 3E1, lacking the neutralizing action, enhanced the growth-suppressive effect of 9D2. The two antibodies were tested as drug delivery vectors. 3E1 was converted into a humanized antibody (h3E1) and conjugated with monomethyl auristatin E (MMAE), a tubulin polymerization inhibitor. When the resulting h3E1–MMAE antibody-drug conjugate (ADC) was added to the standard cultures of CADM1-positive MPM cells, it suppressed the cell growth in a dose-dependent manner. Co-addition of 9D2 enhanced the growth-suppressive effect of h3E1–MMAE ADC. Anti-CADM1 ectodomain antibodies were suggested to serve as both antibody drugs and drug vectors in the treatment of MPM.